Intraoperative Hypotension and Delirium After On-pump Cardiac Surgery. Issue 4 (August 2016) - Wesselink, E. M.; Kappen, T. H.; van Klei, W. A.; Dieleman, J. M.; van Dijk, D.; Slooter, A. J. C.
Abstract : (Abstracted from Br J Anaesth, 115:427–433, 2015) Intraoperative hypotension (IOH) is a possible adverse effect of general anesthesia and may increase risk of postoperative delirium via compromised cerebral perfusion. Delirium, in turn, can lead to prolonged hospital stay and long-term cognitive impairment and mortality.